3D Neurovascular Spheroid for Assessing Hypoxia Induced Blood-Brain Barrier Dysfunction. (16th November 2020) - Wicks, Robert T; Nzou, Goodwell; VanOstrand, Nikki; Mekky, Gehad; Seale, Stephanie; Wicks, Elizabeth; Nechtman, Carl M; Marrotte, Eric; Makani, Vishruti; Murphy, Sean V; Seeds, Michael; Jackson, John; et al.
Abstract: INTRODUCTION: Major hurdles to the development of novel molecular therapies for ischemic stroke are: 1) the lack of an agreed upon in vitro model for high-throughput clinical drug screening and 2) the fundamental differences of BBB organization/architecture between humans and most animal models. The blood-brain barrier (BBB) is a dynamic component of the brain-vascular interface that maintains brain homeostasis and regulates solute permeability. BBB dysfunction plays a critical role in many neurologic disorders including ischemic stroke. METHODS: Spheroids were assembled using a staged-assembly, hanging drop 3D culture method. Once developed, spheroids were cultured in a hypoxic chamber with 0.1% O2 for 24hrs. Spheroids were assessed for cell viability and tight-junction marker expression after removal from hypoxia. Spheroids were then assessed for permeability and pro-inflammatory cytokine production in comparison with normoxic counterparts. Exogenous cytokines delivered to spheroids placed in a normoxic environment caused similar BBB dysruption. Secoisolaricisresinol diglucoside (SDG), a free radical scavenger, and 2-arachidonylglycerol (2-AG), an endocannabinoid anti-flammatory, were then assessed for their prevention of hypoxia-induced neuro-inflammation. RESULTS: Organoids cultured under the hypoxic condition showed increased permeability, pro-inflammatory cytokine production, and increased oxidative stress. The anti-inflammatory agents, SDG and 2-arachidonoyl glycerol, demonstrated protection by reducing inflammatory cytokine levels in the organoids under hypoxic conditions. CONCLUSION: The 3D neurovascular spheroid recapitulates many of the characteristics of BBB dysfunction under hypoxic physiologic conditions and when exposed to exogenous inflammatory mediators. Through the assessment of a free radical scavenger and anti-inflammatory endocannabinoid, we report the utility of the model in screening of potential drug candidates that may reduce the effects of ROS and inflammation after a period of ischemia.